QRIS use Preference by MSME Consumers - Maysha, Maysha; Nathasya, Sri (Gorontalo Development Review, 2024)
This study aimsÂ to examine customer preferences or interests in adopting QRIS (Quick Response QR code Indonesian Standard), which is evaluated based on perceived risk, usefulness, and usefulness, as well as perceived simplicity of use and trust. 277 people responded to the questionnaire that was used to collect the data. We used binary logistic regression analysis to process the data. The study's findings suggest that consumer preferences for adopting QRIS as a method of payment transactions for MSMEs in the city of Surabaya are influenced by views of perceived ease of use, trust, perceived utility, and risk.